2016
DOI: 10.1007/s10792-016-0364-7
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-assisted LASIK versus PRK for high myopia: comparison of 18-month visual acuity and quality

Abstract: Although femto-LASIK induces more HOA compared to PRK-MMC, considering outcomes in terms of 20/20 UDVA, residual refractive error, and CS stability, femto-LASIK provides more favorable results than PRK-MMC in high myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
5
9
1
Order By: Relevance
“…This table reports data before retreats respectively ( Fig. 1f), which is comparable or better than other lower myopia studies [9,16,[23][24][25][26][27][28][29][30][31][32] (Table 3). A better measure of regression effect, than the traditionally reported postoperative SEQ, is the amount of myopic development postoperatively.…”
Section: Complicationssupporting
confidence: 79%
See 1 more Smart Citation
“…This table reports data before retreats respectively ( Fig. 1f), which is comparable or better than other lower myopia studies [9,16,[23][24][25][26][27][28][29][30][31][32] (Table 3). A better measure of regression effect, than the traditionally reported postoperative SEQ, is the amount of myopic development postoperatively.…”
Section: Complicationssupporting
confidence: 79%
“…In the current study, these correlations were not statistically significant at 2 years. The safety index of 1.05 was comparable to lesser myopia studies ( Table 3), suggesting that LVC in VHM has equivalent safety to that of high myopia [16,25,29,36]. As reported elsewhere [6], the high-rate of microstriae (11.9%) can likely be attributed to the very deep ablations (mean 150 μm), although only two eyes with microstriae were deemed to be visually significant requiring intervention.…”
Section: Complicationssupporting
confidence: 66%
“…A meta-analysis by Shortt et al 1 reported that LASIK had superior efficacy and safety compared with PRK; however, the meta-analysis included treatment of eyes with low to high myopia with different treatment techniques. Hashemi et al 20 demonstrated that UCVA improved faster and better after femtosecond-assisted LASIK compared with PRK with mitomycin C with a follow-up duration of 6 months. Both procedures were similar in safety profile but efficacy was better after LASIK with an efficacy index of 0.99 vs 0.93 for PRK.…”
Section: Discussionmentioning
confidence: 99%
“…This was unlike our study which catered to a wider range of refractive errors, including high myopes. This could explain the difference in the outcomes as it has been seen in multiple studies that FAL is superior in those with high myopia [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%